Multipurpose Incubator Based on Microcontroller System With Distance Monitoring Feature Case Study For Crackers Drying - Supriyono, Heru; Juliana, Anik; Supardi, Agus; Kurnia, Pramudya; Ananta, Muhammad Satria; Nugroho, Mohammad Dwiki Aji; Hidayatullah, Helmi (Journal of Applied Engineering and Technological Science (JAETS), 2025)
Most available commercial incubators are considered not appropriate for certain food processing such as for crackers drying and also considerably expensive. Besides, they do not have distance monitoring and control features. The objective of this article is to present the development process of an incubator prototype which has distance monitoring and control feature built based on the components commercially available in the market involving  traditional stove-based oven, electric heater, DHT22 temperature sensor, ESP8266 microcontroller, buzzer, and LCD OLED display. The incubator was equipped with the Blynk platform of a smartphone for distance control and monitoring. The functional test results showed that the developed incubator works well as expected. The calibration testing results suggested that temperature measurement by using the developed system has inaccuracy of 0.34% when compared to measurement by using a commercial thermometer. To validate its function in actual condition, the incubator was used for drying rice crackers. The rice crackers were dried at the temperature of 70  with a duration of 5 hours. It can be observed that the drying result by using the developed incubator was comparable to that of drying by direct sunlight on a sunny day with a duration of 16 hours.